Application for Calculation of Islamic Sharia Inheritance Based on Android for Mawaris Fiqh Courses - Anwar, Artesia; Darmawati, Gusnita (Knowbase : International Journal of Knowledge in Database, 2021)
This research was motivated by the discovery of problems in terms of calculating inheritance in the Mawaris Fiqh course at the Islamic Family Law Department of IAIN Bukittinggi, the calculation of inheritance in the Maris Fiqh course still uses the manual method, in which lecturers and students still have to calculate using pen and paper how much the number of shares of each person entitled to inheritance rights. The purpose of this research is to design an Android-Based Application for Inheritance Calculation of Islamic Law for Fiqh Mawaris Subject, Islamic Family Law Department, Sharia Faculty IAIN Bukittinggi, which is practical, effective and efficient. The method used in this research is Research and Development, better known as (R&D). 4D Models (Define, Design, Develop, Disseminate). The system development model used is the System Development Life Cycle (SDLC). The model used in this SDLC is the waterfall, namely Communication, Planning, Modeling, Construction, and Development. The programming language used is the PHP programming language. The product test used is the Test of Validity, Test of Effectiveness and Test of Practicality. The system that has been designed has been tested and has been declared valid, effective and practical in its use. The results of the product test that the author did obtain a validity test from 3 experts obtained a value of 0.80 with a valid category, a practicality test from 5 practitioners obtained a value of 0.93 in a very high category, and test effectiveness of 5 appraisers obtained a value of 0.86 effective categories.